2010
DOI: 10.1002/elan.201000236
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrocatalytic Performance of Anthraquinonemonosulfonate‐Doped Polypyrrole Composite: Electroanalysis for the Specific Roles of Anthraquinone Derivative and Polypyrrole Layer on Oxygen Reduction Reaction

Abstract: To analyze the specific roles of anthraquinone-2-sulfonate (AQS) and polypyrrole (PPy) layer on oxygen reduction reaction (ORR), the electrocatalytic reduction of oxygen was investigated on the AQS/PPy composite modified graphite electrode. Results show that the enhanced electrocatalytic performance is attributed to the excellent electrocatalytic activity of the immobilized AQS functional groups to mediate two-electron reduction of O 2 to H 2 O 2 . The PPy layer may not participate in ORR, but it can further c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The electrocatalytic H 2 O 2 synthesis cell equipped with AQ–C 3 N 4 GDE developed in this study achieved H 2 O 2 generation at 60.1 mmol g catalyst –1 h –1 , which is 4.3 times higher than in the case of AQ–C 3 N 4 in a conventional immersed electrode setup and 20.2 times higher than in the case of bare C 3 N 4 GDE without AQ. This performance marks a significant improvement over previous electrocatalysts that utilize AQ as active catalytic centers which previously suffered from either a low yield (<10 mmol g catalyst −1 h −1 ) and efficiency (<30%) or an excessively high overpotential requirement (1.4 V) . We attribute the observed improvement to two critical modifications introduced in this study.…”
Section: Discussionmentioning
confidence: 61%
“…The electrocatalytic H 2 O 2 synthesis cell equipped with AQ–C 3 N 4 GDE developed in this study achieved H 2 O 2 generation at 60.1 mmol g catalyst –1 h –1 , which is 4.3 times higher than in the case of AQ–C 3 N 4 in a conventional immersed electrode setup and 20.2 times higher than in the case of bare C 3 N 4 GDE without AQ. This performance marks a significant improvement over previous electrocatalysts that utilize AQ as active catalytic centers which previously suffered from either a low yield (<10 mmol g catalyst −1 h −1 ) and efficiency (<30%) or an excessively high overpotential requirement (1.4 V) . We attribute the observed improvement to two critical modifications introduced in this study.…”
Section: Discussionmentioning
confidence: 61%
“…25 Previous research indicated that AQS could serve as an electron shuttle to accelerate electron transfer 41 and also as an electron mediator for enhanced electrocatalytic performance. 42…”
Section: The Effect Of Dopants On the Performance Of Polythiophene/znmentioning
confidence: 99%
“…In addition, PPy has been used to enhance the electrocatalytic performance of anthraquinones and the derivatives towards ORR. The researchers incorporated the anthraquinones into the PPy matrix as doping species by electropolymerizing pyrrole in a 0.5 M H 2 SO 4 aqueous solution containing both pyrrole and anthraquinones [75][76][77] or sequential electropolymerization of pyrrole and electrodeposition of anthraquinones, 78 and comparative studies demonstrated that the ORR catalytic activity of anthraquinones in acidic media could be apparently improved by reducing the overpotential and enhancing the peak current through immobilizing them into a PPy matrix. It was shown that PPy has little impact on the twoelectron-transfer ORR mechanism of anthraquinones, while it is only used as an electron transfer matrix and protective layer for long term stability.…”
Section: Metal-free Catalystsmentioning
confidence: 99%